Anthropometric and physical performance characteristics in African women football players: A prospective, cross-sectional pilot study - Mkumbuzi, N. S.; Chibhabha, F.; Govere, F. M.; Chiwaridzo, M.; Oulo, B. (Central European Journal of Sport Sciences and Medicine, 2022)
Being injured is inherent to participating in football activities; therefore, prevention of injuries is crucial. This requires that the risk factors for injury be established. However, such studies are rarely conducted in women athletes in Africa. The study`s aim was to explore intrinsic risk factors for injury among African women football players using functional and musculoskeletal assessments. Participants (n=40) completed demographic questionnaires; upper and lower limb active range of motion (AROM); muscle endurance and functional movement screening (FMS™) assessed. Median age [Q1; Q3] was 24 [20; 27] years. Participants performed 20.5 [0; 30.5] push-ups and 28 squats [30; 38] in 60s; and held the prone elbow plank for 46.2s [30.6; 64.5]. Median FMS™ score was 12 [10; 13]; most players (n=27, 68%) could not execute a proper deep squat. Most players (70%; n=28), were able to properly perform the in line lunge but scored poorly in the shoulder mobility domain of the FMS™, with 73% (n=29) scoring =1. Players with a history of injury had lower FMS™ total (p=0.02). Overall, participants presented with low muscle endurance and movement imbalances, which might predispose them to injury. Hence, strength and conditioning measures should be instituted in this population to prevent injuries.